Upaya Mengatasi Bullying melalui Edukasi Pendidikan Karakter - Anggraini, Ratna Dwi; Nopriansyah, Untung; Setiawan, Rendi; Adelia, Anggita; Arinda, Devi; Maharani, Putri (LPPM STKIP PGRI Pacitan, 2024)
Bullying is a form of child abuse that is perpetrated by peers against someone (child) who is